A 6‐month prospective randomized controlled trial of remotely delivered group format epilepsy self‐management versus waitlist control for high‐risk people with epilepsy. (10th August 2018) - Sajatovic, Martha; Colon‐Zimmermann, Kari; Kahriman, Mustafa; Fuentes‐Casiano, Edna; Liu, Hongyan; Tatsuoka, Curtis; Cassidy, Kristin A.; Lhatoo, Samden; Einstadter, Douglas; Chen, Peijun
Summary: Objective: Despite advances in care, many people with epilepsy have negative health events (NHEs) such as accidents, emergency department visits, and poor quality of life. "S elf‐ma nagement for people wit h epilepsy and a history of negative health events" (SMART) is a novel group format epilepsy self‐management intervention. A community participatory approach informed the refinement of SMART, which was then tested in a 6‐month randomized controlled trial of SMART (n = 60) versus waitlist control (WL, n = 60). Methods: Participants were adults aged ≥18 years with epilepsy and an NHE within the past 6 months (seizure, accident, self‐harm attempt, emergency department visit, or hospitalization). Assessments were conducted at screening, baseline, 10 weeks, and 24 weeks (6 months). Primary outcome was 6‐month change in total NHE count. Additional outcomes included depression on the nine‐item Patient Health Questionnaire and Montgomery‐Asberg Depression Rating Scale, quality of life on the 10‐item Quality of Life in Epilepsy, functioning on the 36‐item Short‐Form Health Survey, and seizure severity on the Liverpool Seizure Severity Scale. Results: Mean age was 41.3 years (SD = 11.82), 69.9% were African American, 74.2% were unemployed, and 87.4% had an annual income < US$25 000; 57.5% had a seizure within 30 days of enrollment. Most NHEs were seizures. Six‐month study attrition was 14.2% overall and similar between arms. Individuals randomized to SMART had greater reduction in total median NHEs from baseline to 6 months compared to WL ( P  = 0.04). SMART was also associated with improved nine‐item Patient Health Questionnaire ( P  = 0.032), Montgomery‐Asberg Depression Rating Scale ( P  = 0.002), 10‐item Quality of Life in Epilepsy ( P  < 0.001), and 36‐item Short‐Form Health Survey ( P  = 0.015 physical health, P  = 0.003 mental health) versus WL. There was no difference in seizure severity. Significance: SMART is associated with reduced health complications and improved mood, quality of life, and health functioning in high‐risk people with epilepsy. Additional efforts are needed to investigate potential for scale‐up.